PENGARUH PENGGUNAAN SITUS JEJARING SOSIAL TERHADAP MOTIVASI BELAJAR MAHASISWA PRODI PENDIDIKAN EKONOMI FKIP UNTAN 2015 - Sartini, Sartini; Nuraini, Nuraini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the use of social networking sites on the motivation of student learning Economic Education Program FKIP Untan Force 2015. The research method used is descriptive quantitative method with the form of correlation research. The sample of research is 36 students of PPAPK Economic Education FKIP Untan Pontianak force 2015. The data collection tool used is questionnaire and literature / document. The result of the research shows that (1) the use of social networking site of the students of Economic Education Program FKIP Untan Angkatan 2015 has a percentage of 76.66% belongs to the high category (2) student learning motivation FKIP Education Program Untan Force 2015 has a percentage of 59.97 % is categorized enough (3) there is influence of usage of social networking site to student motivation Study Program Economic education FKIP Untan Force 2015 with value of t count> t table (3,232> 2,032) and significance value 0,003 <0,005, hence Ho refused and Ha accepted (4) the amount of influence of the use of social networking sites on student learning motivation FKIP Education Education Program Untan Force 2015 by 23.5%. Keywords: Use of Social Networking Sites, Learning Motivation, Economics Education Students